Hunger: A Missed Opportunity for Screening in the Pediatric Emergency Department. (October 2018) - Robinson, Tamar; Bryan, Leah; Johnson, Veda; McFadden, Terri; Lazarus, Sarah; Simon, Harold K.
Background . The American Academy of Pediatrics and pediatric community recognize the importance of addressing social determinants of health. There are limited data on the prevalence of food insecurity or literature establishing protocols assessing food insecurity in the emergency department (ED). Methods . Two anonymous surveys were administered, one to families during their ED visit and another to ED staff to assess perceptions on the ED's role in providing social support. Results . Thirty-three of 214 respondents (15.4%) reported food insecurity and are associated with economic risk factors ( P < .0001) and a lack of primary care ( P = .008). Overall, 83.2% of the ED staff believed knowing information about families' social risk factors would help patient care and 77.6% believed that the ED staff should address families' social needs. Conclusions . Food insecurity affects a significant portion of ED families across income ranges. Screening for food insecurity in the ED is important given association with lack of primary care. Hospital staff supports screening and intervention.